2018
DOI: 10.3389/fpsyg.2018.00463
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Recognition as a Real Strength in Williams Syndrome: Evidence From a Dynamic Non-verbal Task

Abstract: The hypersocial profile characterizing individuals with Williams syndrome (WS), and particularly their attraction to human faces and their desire to form relationships with other people, could favor the development of their emotion recognition capacities. This study seeks to better understand the development of emotion recognition capacities in WS. The ability to recognize six emotions was assessed in 15 participants with WS. Their performance was compared to that of 15 participants with Down syndrome (DS) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…However, recent studies that examined the developmental trajectory of facial expression recognition in children with WS and TD children would provide another perspective on facial emotion recognition in children with WS. Ibernon et al (2018) revealed that correct awareness of facial expression in children with WS improved as their non‐verbal developmental age matured when tested by non‐verbal tasks, while Martínez‐Castilla et al (2015) revealed correct awareness of facial expression in children with WS did not improve as their chronological or mental age matures when tested by verbal tasks. Importantly, the developmental trajectory of non‐verbal tasks of facial expression recognition, not verbal tasks, was the same as TD children (Ibernon et al, 2018).…”
Section: Development Of Emotion Understanding In Atypically Developin...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies that examined the developmental trajectory of facial expression recognition in children with WS and TD children would provide another perspective on facial emotion recognition in children with WS. Ibernon et al (2018) revealed that correct awareness of facial expression in children with WS improved as their non‐verbal developmental age matured when tested by non‐verbal tasks, while Martínez‐Castilla et al (2015) revealed correct awareness of facial expression in children with WS did not improve as their chronological or mental age matures when tested by verbal tasks. Importantly, the developmental trajectory of non‐verbal tasks of facial expression recognition, not verbal tasks, was the same as TD children (Ibernon et al, 2018).…”
Section: Development Of Emotion Understanding In Atypically Developin...mentioning
confidence: 99%
“…Ibernon et al (2018) revealed that correct awareness of facial expression in children with WS improved as their non‐verbal developmental age matured when tested by non‐verbal tasks, while Martínez‐Castilla et al (2015) revealed correct awareness of facial expression in children with WS did not improve as their chronological or mental age matures when tested by verbal tasks. Importantly, the developmental trajectory of non‐verbal tasks of facial expression recognition, not verbal tasks, was the same as TD children (Ibernon et al, 2018). Although it remains difficult to conclude, there may be different developmental processes or mechanisms for facial expression recognition in TD children and those with ASD and WS, especially when assessing by verbal task.…”
Section: Development Of Emotion Understanding In Atypically Developin...mentioning
confidence: 99%